(untitled) (مجلة جامعة اللاذقية - سلسلة العلوم الصحية, 2016)
يهدف البحث الى التعرف على العلاقة بين القياسات الجسمية (الوزن والطول الكلي وطول الطرف السفلي) ودقة التهديف عند اللاعبين الناشئين وقد تم استخدام المنهج الوصفي بإسلوب العلاقات الارتباطية، أما عينة البحث فقد تضمنت 15 لاعب في كرة القدم من اللاعبين الناشئين في نادي جبله الرياضي وتم افتراض وجود علاقة ذات دلاله احصائي بين بعض القياسات الجسمية (الوزن وطول الجسم الكلي وطول الطرف السفلي) ودقه التهديف في كرة القدم لدى لاعبي كره القدم الناشئين . واستخدمت الوسائل الاحصائية المناسبة وتم التوصل الى عدم وجود علاقة ارتباط معنويه بين القياسات الجسمية المدروسه ودقة التهديف في كرة القدم ، وقد أوصى الباحث بما يلي : 1- إجراء دراسات مماثلة على فئات عمرية متقدمة ومهارات مختلفة في كرة القدم . 2- اجراء دراسات مشابهه على باقي مهارات كرة القدم . The research aims at identifying the relationship between Relationship of Some Physical Measurements (Weight, Total Height and Length of the Lower Limb) with Junior Footballers Accurate Scoring. The descriptive methodology has been used in the style of correlation relationship. The research sample included the 15 footballers from the youngsters in Jableh Sports Club. An assumption has been established of a relationship of statistical significance between Relationship of Some Physical Measurements (Weight, Total Height and Length of the Lower Limb) with Junior Footballers Accurate Scoring. The suitable statistical tools, used in this research, shows the absent of meaningful relationship between Some Physical Measurements (Weight, Total Height and Length of the Lower Limb) with Junior Footballers Accurate Scoring. The researcher recommends the following: 1- conduct similar studies on different age groups and advanced skills in football 2- conduct similar studies on other football game skills